36 Type 1 interferon and endothelial progenitor cell function: development of an in vitro endothelial model of systemic lupus erythematosus. Issue 20 (23rd September 2011) - Reynolds, J A; Williamson, K; O'Neill, T; Ray, D W; Bruce, I N; Alexander, M Y
Abstract : Systemic Lupus Erythematosus (SLE) is associated with an increased risk of cardiovascular disease. Endothelial dysfunction in SLE correlates with circulating interferon (IFN) levels. Late-outgrowth endothelial progenitor cells (LO-EPCs) from lupus patients have impaired function which correlates with an increased expression of IFN-response genes (the IFN-signature). We aim to establish an in vitro model of SLE endothelial pathology, using IFN-α treatment of LO-EPC and human aortic endothelial cells (HAoEC), to develop novel preventative or reparative strategies for this disease. Late-outgrowth EPCs were isolated from human umbilical cord blood and characterised by immunocytochemistry and RT-PCR. HAoECs were cultured using standard protocols. Cell proliferation and tubule formation was analysed by MTT and Matrigel assays respectively. Connected tubes and branch points were counted 18 h after treatment with IFN2b or serum from SLE patients. Current studies involve establishing the interferon signature in endothelial cells, using a combination of microarray and Bioplex analysis. IFN-α-2b (10 ng/ml) results in reduced tubule formation by LO-EPCs but not HAoECs. SLE serum inhibits the proliferation of LO-EPCs but not HAoEcs in a dose-dependent manner. However, proliferation was not affected in either cell type by the addition of IFN-α-2b at concentrations up to 100 ng/ml at 24, 48 or 72 h. LO-EPCs are significantly affected in terms of their tube-forming capacity and proliferative response to IFN-α-2b and SLE serum respectively, while mature HAoECs lack this response to IFN2b. We conclude that LO-EPCs could be a target cell in SLE and offer a potential model for development of vasculoprotective therapies in these patients.